Equilibrium binding constants of Tris-(3,4,7,8-Tetramethyl-1,10-phenanthroline)Iron(II) Sulphate and Tris-(4,7- dimethyl-1,10-phenanthroline)Iron(II) Perchlorate with Sodium Dodecyl Sulphate. A comparative study - Latona Dayo, Felix (جامعة الوادي - university of el oued, 2021)
Binding constants were investigated with a double beam unicam UV-Visible spectrophotometer at maximum absorption peaks (λmax) of 500nm and 510 nm for tris– (3,4,7,8 – tetramethyl -1,10- phenanthroline)iron(II) sulphate and Tris- (4,7-dimethyl –1,10 – phenanthroline)iron(II) perchlorate, respectively and the data were analyzed using double reciprocal plots. Absorbances were taken at fixed concentration of the metal complexes and the concentrations of sodium dodecyl sulphate (SDS) were far less than the critical micelle concentration (CMC). The effect of alkaline, acid, benzoate ion and urea on binding constants were investigated. Binding between Tris-(4,7-dimethyl-1,10-phenanthroline)Iron(II) Perchlorate(Fe(Me2phen)32+ and Sodium dodecyl sulphate was accelerated at low [H+] = 1.00 10-4 mol dm-3 and decreased at higher acid concentrations. However, binding was enhanced in the presence of hydroxyl ion, benzoate ion and urea. Furthermore, binding between Tris-(3,4,7,8-Tetramethyl-1,10-phenanthroline)Iron(II) Sulphate and sodium dodecyl sulphate was accelerated at low[H+] = 1.00 10-4 mol dm-3 to reach a maximum at [H+] = 2.00 x 10-4 mol dm-3 after which it decreased at higher acid concentrations. However, binding was retarded in the presence of hydroxyl ion and urea but enhanced in benzoate ion.
Article
Keywords: Tris-(3,4,7,8-Tetramethyl-1,10-phenanthroline)Iron(II) Sulphate (Fe(Me4phen)32+); Tris-(4,7- dimethyl-1,10-phenanthroline)Iron(II) Perchlorate(Fe(Me2phen)32+); Sodium Dodecyl Sulphate (SDS); Equilibrium binding constants